The Relationship between ASD Symptomology, Performance, Experienced Problems and Benefits in Problem Based Learning (PBL) Curricula - de Groot, Kristel (Student Undergraduate Research E-journal!, 2015)
The attention for supporting students with Autism Spectrum Disorders (ASDs) at university has recently grown. However, no research to date has looked into the fit between ASD and a specific form of education, Problem-Based Learning (PBL). The current study uses a newly developed questionnaire that focuses on the four elements of PBL: constructive, self-directed, collaborative, and contextual learning. The questionnaire showed to be highly reliable. Although higher ASD symptomology predicted reported experience of more problems and fewer benefits of PBL, these experiences were not accompanied by lower grades. This indicates that ASD students benefit from working in PBL.